An Analysis of Open Science Action Plans by Canadian Federal Science Departments and Agencies - Ripp, Chantal; Hare, Madelaine; Cobey, Kelly; Haustein, Stefanie (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie, 2025)
Following the release of the Roadmap for Open Science in 2020, Canadian federal departments and agencies that produce or fund scientific research were tasked with developing open science action plans. This study investigates the content and planned implementation of eleven publicly available action plans as of October 2024 using cross-sectional mapping and thematic analysis. The results are examined alongside the Roadmap’s recommendations that directly implicate departments and agencies, including consultations with federal scientists, open access to publication, and enabling FAIR data principles. This study provides insights into how open science activities are understood and operationalized in Canada at the federal level and how the government intends to address obstacles impeding access to federal research. A diversity of approaches to implementing open science practices was observed, along with persistent challenges, including limited mandates for oversight, uneven adoption among smaller departments, and a lack of integration between open science goals and existing research assessment systems. Opportunities lie in strengthening institutional coordination, enhancing horizontal accountability mechanisms, and aligning incentives with open science practices.